REDUÇÃO DA MAIORIDADE PENAL - Caldeiras, Alécio Alves; Ribeiro, Alessandra dos Santos; Oliveira, Fernando Razzaboni de; Gomes, Gabriela Helena da Silva; Nascimento, Renan Cardoso; Beserra, Luis Carlos Leandro; Macena, Lincoln Villas Boas (Revista Ciências Jurídicas e Sociais - UNG-Ser, 2014)
... ver texto na íntegra.